Courtxpert hub: court reservations & equipment platform - Lim, Xin Yee (2025)
The CourtXpert Hub project addresses the critical gaps in existing sports court booking systems within Malaysia, particularly in Kampar, Perak. Despite the availability of booking services across Malaysia, current systems such as Courtsite, AFA, 7Stone, and IOI Sports Centre lack integrated Smart dashboa options, multilingual accessibility, and an advanced administrative dashboard. These shortcomings often lead to inconvenience for casual players, reduced inclusivity among multilingual users, and inefficient decision-making by administrators. To overcome these limitations, the proposed platform was enhanced with three major features: an equipment rental prompt, a smart administrative dashboard with predictive analytics, and multilingual support in English, Bahasa Melayu, and Chinese. The system was developed on a PHP–MySQL architecture with Stripe API integration for secure payments (Visa, FPX, and GrabPay). The methodology followed an Agile, incremental development approach, incorporating iterative design, testing, and refinement throughout the process. Moreover, system evaluation demonstrated reliable booking workflows, real-time equipment inventory management, and accurate predictive insights into revenue and venue utilization. In addition, administrators were also equipped with customer retention analytics and re-engagement tools, such as WhatsApp messaging integration, to improve user loyalty. As a result, the findings confirm that CourtXpert Hub successfully achieves its objectives by providing a comprehensive, inclusive, and intelligent booking platform. It not only improves user accessibility and convenience but also empowers administrators through data-driven decision-making tools. The project contributes to the digitalization of sports facility management in Malaysia and lays the foundation for scalable, nationwide deployment.